Invitation to public speaking - Griffin, Cindy L. (Stamford, [Connecticut] : Cengage Learning, 2015)
Describes how to deliver a speech in different situations, with considerations of the art of listening, topic selection, audience, speech components, types of speeches, and visual aids.
Previous edition : 2012.
Received for cataloging, August 2014 ; edition statement from cover.
Keywords: Public speaking